Image on Internet as a Strategy of Rejuvenation: Virtual Expectations - Díaz Rodríguez, Pablo; Santana Talavera, Agustín; Rodríguez Darias, Alberto Jonay (Quaderns de l’Institut Català d’Antropologia, 2016)
Fuerteventura (Canary Isles, Spain) has historically been characterized as a tour-ist destination with a consolidated ‘sun, sand and sea’ image. Recent studies reveal the existence of important socio-environ-mental saturation symptoms that warn of the need for a change of course. The tour-ism sector is currently trying to promote the idealization of new visitors through renovation strategies of its projected im-age. These images are revealed as an important cultural mediation mechanism that influences the conformation of power structures. This article examines the processes of resignification that involves the creation of these images. Therefore, quantitative and qualitative techniques are combined in the analysis of the con-tents, strategic codes and ideological nar-ratives present in the discourses of the most visited websites of Administration, enterprises and tourists from its main tourism source markets. The projection of four underlying cultural images is re-vealed: i) paradise place; ii) remote des-tination; iii) primitivism; iv) traditionalism, all of which would be framed in turn in the projection of an overall image of Fuerteventura as an ideal coastal desti-nation. These images contain ideological discourses that seek to transform certain resources into cultural merchandising, covering in them dynamics of cultural identification which can generate effects on self images of local populations.